NTECH AND YOUTH EMPOWERMENT IN BAYELSA STATE, 2019 – 2023 - Kolokolo, Francis (Journal of Social Science, 2025)
Objective: This study investigates the N-Tech and youth empowerment initiatives in Bayelsa State from 2019 to 2023, focusing on the N-Power Tech program. It seeks to explore the significance of the program, the factors that led to its establishment, and its effects on poverty alleviation and unemployment. Method: Employing a qualitative research framework, the study used a conventional methodology, with thematic analysis to examine data related to public policy, youth empowerment, and the N-Power initiative. Results: The findings revealed a strong correlation between the N-Power Tech program and the reduction of unemployment and poverty in Bayelsa State. It further highlighted the importance of rural development through this initiative to address the needs of the rural population, which constitutes a large part of the state's demographic. Novelty: This study contributes to understanding the role of human capital development through government-led initiatives such as N-Power Tech, emphasizing the need for political neutrality and awareness campaigns to maximize the program’s impact. It also advocates for targeted rural development to enhance the socio-economic well-being of the state.